2014
DOI: 10.7600/jpfsm.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cell heterogeneity and hierarchy in skeletal muscle

Abstract: Satellite cells are skeletal muscle tissue stem cells located between the basal lamina and sarcolemma of myofibres and play crucial roles in adult muscle repair and regeneration as well as postnatal muscle growth. More and more findings indicate that satellite cells exist as a genetically and functionally heterogeneous population among muscles, which is not only based on fibre types, but also embryonic origin. Satellite cells are also a heterogeneous population even within a single myofibre. Only a small popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Satellite cells are mitotically quiescent in healthy adult muscle, but are activated in response to stimulation, such as muscle damage, to differentiate into myoblasts and proliferate extensively (Ono 2014). Quiescent satellite cells express the transcription factor Pax7 in adult muscle.…”
Section: Muscle Stem Cell Functions Are Impaired In An Estrogen-deficmentioning
confidence: 99%
“…Satellite cells are mitotically quiescent in healthy adult muscle, but are activated in response to stimulation, such as muscle damage, to differentiate into myoblasts and proliferate extensively (Ono 2014). Quiescent satellite cells express the transcription factor Pax7 in adult muscle.…”
Section: Muscle Stem Cell Functions Are Impaired In An Estrogen-deficmentioning
confidence: 99%
“…Muscle satellite cells play a crucial role in providing myonuclei for muscle repair and regeneration in adult muscle [ 21 , 22 ]. Our previous study revealed that prolonged estrogen-insufficient state affected satellite cell function and muscle regeneration in OVX female mice [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tissue stem cells in adults retain the ability to proliferate, self‐renew, and differentiate throughout life to maintain tissue homeostasis and repair injuries. Understanding how the balance between self‐renewal and differentiation is regulated in satellite cells is central to elucidating how skeletal muscle maintains a stem cell pool and homeostasis throughout life (Relaix and Zammit ; Ono ; Wang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite cells are responsible for providing myonuclei for postnatal muscle growth, hypertrophy, repair, and regeneration in adults (Otto et al. ; Relaix and Zammit ; Ono ; Wang et al. ).…”
Section: Introductionmentioning
confidence: 99%